Exacerbation of acute traumatic brain injury by circulating extracellular vesicles - Hazleton, I; Yates, A; Dale, A; Roodselaar, J; Akbar, N; Ruitenberg, M; Anthony, D; Couch, Y (Mary Ann Liebert, 2018)
Inflammatory lesions in the brain activate a systemic acute phase response (APR), which is dependent on the release of extracellular vesicles (EVs) into the circulation. The resulting APR is responsible for regulating leukocyte mobilization and subsequent recruitment to the brain. Factors that either exacerbate or inhibit the APR will also exacerbate or inhibit CNS inflammation as a consequence, and have the potential to influence ongoing secondary damage. Here, we were interested to discover how the circulating EV population changes after traumatic brain injury (TBI) and how manipulation of the circulating EV pool impacts on the outcome of TBI. We found the number of circulating EVs increased rapidly after TBI, and this was accompanied by an increase in CNS and hepatic leukocyte recruitment. In an adoptive transfer study, we then evaluated the outcomes of TBI after administering EVs derived from either in vitro macrophage or endothelial cell-lines stimulated with LPS, or from murine plasma from an LPS-challenge using the air-pouch model. By manipulating the circulating EV population, we were able to demonstrate that each population of transferred EVs increased the APR. However, the characteristics of the response were dependent on the nature of the EVs, specifically it was significantly increased when animals were challenged with macrophage-derived EVs, suggesting that the cellular origins of EVs may determine their function. Selectively targeting EVs from macrophage/monocyte populations is likely to be of value in reducing the impact of the systemic inflammatory response on the outcome of traumatic CNS injury.